Odpowiedź:
1.
a)
(-7)² + (-1)² = 49 + 1 = 50
b)
(-6 - 4)² - 2² = (-10)² - 4 = 100 - 4 = 96
c)
(-8)² - (-3)³ = 64 - (-27) = 64 + 27 = 91
d)
(6 - 10 + 12)² - (-4 + 5)³ = 8² - 1³ 64 - 1 = 63
e)
(-1/2)² - (-4/5)^0 = 1/4 - 1 = -3/4
f)
(1 1/2)³ - (-1/2)² = (3/2)³ - 1/4 = 27/8 - 2/8 = 3 3/8 - 2/8 = 3 1/8
g)
(-1,2)² - (-1,44)^1 = 1,44 + 1,44 = 2,88
h)
(-0,1)³ + (2,3)² = -0,001 + 5,29 = 5,289
2.
a)
3³ - (-2)^4 = 27 - 16 = 11
b)
-4² - (-10)^0 = -16 - 1 = -17
c)
-[-(-5)² + (-1)³] = -(-25 - 1) = -(-26) = 26
d)
(-6)³ + (-3)^6 = -216 + 729 = 513
e)
-5² + 2^5 = -25 + 32 = 7
f)
-[-(-4)³ - 3^4] = -(64 - 81) = -(-17) = 17
g)
-(-8)² - [-(-3)²]³ = -64 - (-9)³ = -64 + 729 = 665
h)
-125^0 - (-5)³ = -1 + 125 = 124
Szczegółowe wyjaśnienie: